PENGARUH KUALITAS PELAYANAN ADMINISTRASI KEPENGURUSAN KARTU IDENTITAS PENDUDUK MUSIMAN (KIPEM) TERHADAP TINGKAT KEPUASAN MASYARAKAT (Studi pada Dusun Bun, Kelurahan Dangin Puri, Kecamatan Denpasar Timur, Kota Denpasar) - Irawati, Dessy (CITIZEN CHARTER, 2014)
ABSTRACK This research takes its background from the increasing growth of population in the city of Denpasar is mainly caused by the migration factor. Migration or movement of people is a difficult thing to be avoided by living things, including humans . Sometimes the movement is going on without any prior planning. Sometimes migration is done in a way that is deliberate as a shortcut to get to a direction of success coveted by everyone . It is on the one hand , a new problem in the administration sector of population that is associated with the administration of KIPEM.The concept of service quality a concept that includes the value of internal and external about formation of a system of services that are associated with public satisfaction. This concept contains variables KIPEM Service Quality Leadership (X) as an independent factor and Public Satisfaction (Y) as the dependent variable. The research shows as follows: (1) there is a simultaneously significant influence mostly from service quality variable to the public satisfaction. R Square(R2) is 0,943. It can be concluded that the influence of service quality concept through the public satisfaction can be 93,3% by service quality (X). (2) F-test shows that variables of service quality influence significantly to the public satisfaction. This can be seen from F-count that is 80,041 with the rate of significance 0, 000. Therefore, the variables of service quality (X) influence the public satisfaction (Y) significantly. Â  Keywords: quality service, community satisfaction